2016
DOI: 10.1002/adma.201505122
|View full text |Cite
|
Sign up to set email alerts
|

Graphene Oxide Liquid Crystals: Discovery, Evolution and Applications

Abstract: The discovery and relevant research progress in graphene oxide liquid crystals (GOLCs), the latest class of 2D nanomaterials exhibiting colloidal liquid crystallinity arising from the intrinsic disc-like shape anisotropy, is highlighted. GOLC has conferred a versatile platform for the development of novel properties and applications based on the facile controllability of molecular scale alignment. The first part of this review offers a brief introduction to LCs, including the theoretical background. Particular… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
149
0
2

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 224 publications
(156 citation statements)
references
References 138 publications
1
149
0
2
Order By: Relevance
“…The non-woven configuration is convenient to reach an adequate packing density, thus facilitating the integral fabric performance, and is technically viable for industrial production of GFFs. Graphene fibres were prepared using a wet-spinning protocol1181920. To realize interfibre bonding, we initiate a wet-fusing assembly approach based on self-assembly of the as-prepared GO fibres.…”
Section: Resultsmentioning
confidence: 99%
“…The non-woven configuration is convenient to reach an adequate packing density, thus facilitating the integral fabric performance, and is technically viable for industrial production of GFFs. Graphene fibres were prepared using a wet-spinning protocol1181920. To realize interfibre bonding, we initiate a wet-fusing assembly approach based on self-assembly of the as-prepared GO fibres.…”
Section: Resultsmentioning
confidence: 99%
“…The conductivity of our optimal PUHC composite is compared to previous reports of conducting PU composites in Table 2 . The increase in conductivity may be due to the establishment of LC structure in PUHC (transfer isotropic to nematic structure) . Percolation threshold results comparing the electrical behavior of LCGO and PEDOT:PSS/LCGO composites suggested that lower amounts of filler are needed to create conducting paths in an isolating matrix of PU.…”
Section: Resultsmentioning
confidence: 99%
“…At above a critical concentration, GO/polymer dispersion can form a self-aligned ordered structure as a result of configurational-entropy driven excluded volume interactions between the GO sheets and the high affinity between the polymer wrapped amphiphilic GO sheets. 34 Especially, the extremely high aspect ratio (∼ 15000) of GO sheets induced a highly anisotropic (aligned) composite film during self-assembly process. Further, it is noted that density of GO is ∼ 2.24 g/cm 3 , while PVDF-HFP possesses density of 1.78 g/cm 3 .…”
Section: Resultsmentioning
confidence: 99%